Children’s coordination of the “sweet spot” when striking a forehand is shaped by the equipment used - Buszard, Tim (Sci Rep, 2020)
Children’s movement coordination is significantly influenced by the equipment used when performing multi-articular actions. Previously we reported that scaled equipment (smaller racket and a softer ball), but not full-sized equipment, promoted a functional coupling between upper arm and forearm angles in children performing a forehand. However, it remains unclear whether the shoulder-racket distance—which is controlled by this coupling—is a performance variable. This study therefore advanced previous research by examining whether the shoulder-racket distance is associated with performance. We also improved our understanding of how the shoulder-racket distance is controlled by including the hand-racket segment in our biomechanical model. Twenty-one children performed 40 forehands in a hitting for accuracy task. Participants were randomly divided into two groups—a scaled equipment group and a full-sized equipment group. Results revealed that the shoulder-racket distance was a performance variable, as evidenced by: (a) its variance reduced closer to ball impact, (b) its distance at ball impact, but not at the start of the forward swing, differentiated good from poor performance, and (c) its distance was similar for both groups, implying that there was a “sweet spot” for striking a ball, regardless of racket size. We also showed that it is the shoulder-racket vector in state-space (i.e., distance and angle) that differentiates good from poor performance. Finally, the manner in which the shoulder-racket distance was controlled differed between the groups, with scaled equipment promoting a more distal control than full-sized equipment. Implications for skill acquisition are discussed.